Tingkat Pengetahuan Mengenai Kepatuhan Minum Obat Pada Pasien Hipertensi Rawat Jalan Di Puskesmas “X” Banyuwangi Tahun 2022 - Isma Oktadiana; Siti Fatimah Sultan; Rena Meutia; Cut Intan Annisa Puteri (Journal of Pharmaceutical and Sciences, 2023)
Hypertension is an increase in blood pressure in the arteries that exceeds normal limits with an increase in systolic blood pressure> 140 mmHg and diastolic blood pressure> 90 mmHg. The level of knowledge about hypertension is one of the factors that can affect adherence to lifestyle and treatment of hypertension. This study aims to determine the level of knowledge and medication adherence in hypertensive patients and to determine the relationship between the level of knowledge on medication adherence in hypertensive patients at the "X" Health Center in Banyuwangi. This research was conducted using a descriptive cross sectional method. Sampling was carried out using purposive sampling method. The results obtained were analyzed using the univariate method based on the patient's demographic characteristics and bivariate using the Spearman test from the SPSS 28 program. The number of patients with outpatient hypertension at the "X" Banyuwangi Health Center for the April-May 2022 period was 80 respondents taken from 100 patients. The results obtained showed that the patient's level of knowledge about hypertension was high at 60% (48 respondents), moderate 33% (26 respondents) and low at 7% (6 respondents). Likewise, the level of adherence to taking medication was also relatively high, namely 88 % (70 respondents), moderate 13% (10 respondents) and low 0% (0 respondents). The conclusion obtained is that there is a very strong and one-way significant relationship between the level of knowledge of the disease and the level of adherence which shows a correlation of 0.900.